2001
DOI: 10.1093/jn/131.11.2848
|View full text |Cite
|
Sign up to set email alerts
|

Oolong Tea Increases Metabolic Rate and Fat Oxidation in Men

Abstract: According to traditional Chinese belief, oolong tea is effective in the control of body weight. Few controlled studies, however, have been conducted to measure the impact of tea on energy expenditure (EE) of humans. A randomized cross-over design was used to compare 24-h EE of 12 men consuming each of four treatments: 1) water, 2) full-strength tea (daily allotment brewed from 15 g of tea), 3) half-strength tea (brewed from 7.5 g tea) and 4) water containing 270 mg caffeine, equivalent to the concentration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
2
9

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(169 citation statements)
references
References 19 publications
7
151
2
9
Order By: Relevance
“…Komatsu et al [32] conducted a randomized, placebo-controlled, crossover trial in 11 healthy females and demonstrated that a single green tea drink containing 156 mg EGCG + 161 mg caffeine and 17 mg polymerized polyphenols increased energy expenditure by 13 kcal / 2hours (5%), whereas oolong tea, containing 81 mg EGCG + 77 mg caffeine, and 68 mg polymerized polyphenols, increased energy expenditure 26 kcal / 2hours (10%). Similarly, Rumpler et al [19] showed that oolong tea (244 mg EGCG + 270 mg caffeine) increased energy expenditure in healthy men 2.9%, for an additional 281 kcal/d over a 3-day period, versus 3.4% (331 kcal/d) for a (270 mg/d) caffeinated water drink.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Komatsu et al [32] conducted a randomized, placebo-controlled, crossover trial in 11 healthy females and demonstrated that a single green tea drink containing 156 mg EGCG + 161 mg caffeine and 17 mg polymerized polyphenols increased energy expenditure by 13 kcal / 2hours (5%), whereas oolong tea, containing 81 mg EGCG + 77 mg caffeine, and 68 mg polymerized polyphenols, increased energy expenditure 26 kcal / 2hours (10%). Similarly, Rumpler et al [19] showed that oolong tea (244 mg EGCG + 270 mg caffeine) increased energy expenditure in healthy men 2.9%, for an additional 281 kcal/d over a 3-day period, versus 3.4% (331 kcal/d) for a (270 mg/d) caffeinated water drink.…”
Section: Discussionmentioning
confidence: 94%
“…Further, reduced food intake following caffeine has been demonstrated [18], suggesting that caffeine can affect both energy intake and energy expenditure. According to Rumpler et al [19], the maximal increase in 24-hour energy expenditure with caffeine, 3-7.2%, occurs at doses of 200-300 mg per day. More than 400 mg of caffeine begins to increase systolic and diastolic blood pressure and is associated with palpitations, anxiety, and dizziness compared to placebo [20].…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that in countries with higher tea consumption like Japan, diabetes is less prevalent (Iso et al, 2006). Some studies have shown a negative correlation between tea consumption and heart disorders and its consequent death (Stensvold et al, 1992;Imai et al, 1995;Duffy et al, 2001;Geleijnse et al, 2002;Hakim et al, 2003) which can be, in large part, attributed to the effects of tea on endothelial function through reducing oxidative stress; but there have been studies in which no relation was observed (Brown et al, 1993; Tea consumption decreased lipid peroxidation in some clinical trials (Klaunig et al, 1999), but was not as effective in the others (Van Het Hof et al, 1999;Hodgson et al, 2000;Rumpler et al, 2001;.…”
Section: Evidence From Human Studiesmentioning
confidence: 99%
“…38 Several studies analyzed the relationship between tea consumption and energy expenditure and found that tea could positively influence energy expenditure, both 24 h and fasting, and fat oxidation in normal-weight adults. 39,40 More studies are needed to confirm the role of tea in weight maintenance, but there are promising results from the published studies. 39,40 Two important factors, however, must be taken into account, the caffeine content in the tea and the addition of sugar.…”
Section: Watermentioning
confidence: 99%
“…39,40 More studies are needed to confirm the role of tea in weight maintenance, but there are promising results from the published studies. 39,40 Two important factors, however, must be taken into account, the caffeine content in the tea and the addition of sugar. Both factors could reduce the potential of tea as a functional food for weight maintenance.…”
Section: Watermentioning
confidence: 99%